Congenital Bands with Intestinal Malrotation after Propylthiouracil Exposure in Early Pregnancy - Alexander A. Leung; Jennifer Yamamoto; Paola Luca; Paul Beaudry; Julie McKeen (Case Reports in Endocrinology)
Exposure to propylthiouracil in early pregnancy may be associated with an increased risk of birth defects. But the spectrum of associated congenital anomalies is not yet well defined. While preliminary reports suggest that most cases of propylthiouracil-associated birth defects are restricted to the preauricular and urinary systems, careful consideration should be given to other possible manifestations of teratogenicity. We propose that congenital bands may potentially represent a rare yet serious complication of propylthiouracil exposure in early pregnancy, possibly arising from an early mesenteric developmental anomaly. We report a case of a 17-day-old girl that presented with acute small bowel obstruction associated with intestinal malrotation arising from several anomalous congenital bands. Her mother was treated for Graves’ disease during pregnancy with first trimester exposure to propylthiouracil but remained clinically and biochemically euthyroid at conception and throughout the duration of pregnancy. This case suggests that the use of propylthiouracil in early pregnancy may be associated with congenital bands and intestinal malrotation. More reports are needed to further support this association.